The Ebola Virus Interferon Antagonist VP24 Undergoes Active Nucleocytoplasmic Trafficking - Angela R. Harrison; Cassandra T. David; Stephen M. Rawlinson; Gregory W. Moseley (Viruses, 2021)
Viral interferon (IFN) antagonist proteins mediate evasion of IFN-mediated innate immunity and are often multifunctional, with distinct roles in viral replication. The Ebola virus IFN antagonist VP24 mediates nucleocapsid assembly, and inhibits IFN-activated signaling by preventing nuclear import of STAT1 via competitive binding to nuclear import receptors (karyopherins). Proteins of many viruses, including viruses with cytoplasmic replication cycles, interact with nuclear trafficking machinery to undergo nucleocytoplasmic transport, with key roles in pathogenesis; however, despite established karyopherin interaction, potential nuclear trafficking of VP24 has not been investigated. We find that inhibition of nuclear export pathways or overexpression of VP24-binding karyopherin results in nuclear localization of VP24. Molecular mapping indicates that cytoplasmic localization of VP24 depends on a CRM1-dependent nuclear export sequence at the VP24 C-terminus. Nuclear export is not required for STAT1 antagonism, consistent with competitive karyopherin binding being the principal antagonistic mechanism, while export mediates return of nuclear VP24 to the cytoplasm where replication/nucleocapsid assembly occurs.